2016
DOI: 10.11648/j.am.20160501.11
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Modeling of Percolation Behavior of Electrical Conductivity in Segregated Network Polymer Nanocomposites Using Monte Carlo Method

Abstract: Polymer nanocomposites filled with carbon nanotubes are observed to present an onset of the insulator-to-conductor transition through previous experimental studies. In this work, numerical simulations based on Monte Carlo method are performed to investigate the percolation threshold. The conductive fillers are modeled as a three dimensional (3D) network of identical units dispersed in the polymer matrix. However, the distribution of the fibers is not uniform due to the existence of the emulsion particles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…The experimental finding that a finite sample density is required for sample stability, i.e compression modulus E c > 0 (figure 9), allows us to make a connection to percolation theory [Gu et al, 2016]. (Eqn.…”
Section: Fibre Network and Percolation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental finding that a finite sample density is required for sample stability, i.e compression modulus E c > 0 (figure 9), allows us to make a connection to percolation theory [Gu et al, 2016]. (Eqn.…”
Section: Fibre Network and Percolation Theorymentioning
confidence: 99%
“…From figure 10a we then obtain that the value of the critical volume fraction φ v,c (φ i ) = ρ c (φ i )/ρ f varies linearly between 0.002 and 0.005. Gu et al [Gu et al, 2016] performed computer simulations of fibre networks. For a fibre aspect ratio of approxamity 57, as for the fibres in our experiments they report a critical volume fraction φ v,c of about 0.005, consistent with our data.…”
Section: Fibre Network and Percolation Theorymentioning
confidence: 99%
“…The integration of separated clusters happen when the concentration of nanotubes approaches a certain critical value. As a result in the system spreading (infinite) cluster is formed, which leads to appearance of the electric contacts between external electrodes in such a compound [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Experimental studies [1] have shown that the conductivity in nanotube polymeric and ceramic matrix materials follows a percolation-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Esse processo foi realizado por meio do arquivo .inp do ABAQUS. (3) Para determinar as coordenadas dos pontos de extremidade da -ésima fibra, é necessário definir com antecedência as coordenadas do seu ponto médio e os ângulos de orientação e , como realizado por Gu et al (2016). ( 1 , 1 , 1 ) e ( 2 , 2 , 2 ) são as coordenadas das extremidades 1 e 2 da -ésima fibra, respectivamente.…”
Section: Geração Das Fibrasunclassified